Measuring Mendicancy: Identifying Capacity for Future Economic Sustainability by Developing a Measure of Government Dependency. (September 2015) - Denny, Lisa; Polkan, Eugene
Abstract Accusations of mendicancy raise the question of government dependency in Australia. This article develops an Age and Economic Activity measure of dependency which incorporates age‐based and behavioural approaches reflecting the various components of dependency: welfare recipients, government employees and youth. Government dependency varies by state and territory and is influenced differently by each component. Analysis accounting for varying age structures fails to explain the differences. Projections of future government dependency to 2050 find increases for all jurisdictions under three scenarios. Policy development to mitigate the fiscal challenges of an ageing population should address the components which influence government dependency.